Isolation and identification of xerophilic fungi on spoiled “Dodol” (Concoction) / Ahmad Muzakkir Rohaizat - Rohaizat, Ahmad Muzakkir (2017)
The aim of the study was to isolate and identify xerophilic fungi from spoiled “dodol” from the market. The colonies of the fungal growth were transferred to the media by surface sampling technique and incubated at 28˚C for five to seven days. Potato dextrose agar was used as media for fungal growth. The fungi then isolated according to their macroscopic characteristics. Both macroscopic and microscopic observations are done on the isolated culture. Microscopic observation was done by using adhesive tape technique before being observed under the microscope. Fungi isolated are Aspergillus and Penicillium species. Morphological observation was done to observe fungi on the spoiled ‘dodol’.